Riemann–Hilbert boundary value problem for multidimensional elliptic systems of equations - Paliokas, Eugenijus (Lietuvos matematikos rinkinys, 2023)
Multidimensional analogues of Cauchy–Riemann quations and of Riemann–Hilbert boundary value problem are studied. Their relation to the scalar boundary value problem is demonstrated.
Keywords: elliptic systems; boundary value problems; Riemann–Hilbert problem